Age analysis of Rio swimming finalists: The older the better! - Madge, R. (2016)
This article looks at the age statistics for Rio 2016 and London 2012 Olympic finalists in swimming. The author also also compares these data to the ages for 2016 Olympic Trial finalists from Canada, Australia, Britain, Japan, Russia and Brazil.